Structural fire engineering - Lennon, Tom, 1963- (ICE, 2011)
Providing comprehensive and practical design guidance on the application of structural fire engineering to specialist structural engineers, this book explains structural fire engineering design process, its position within the regulatory system and guidance on the selection of appropriate partial factors for the fire limit state for variations in material properties and loading.